2012
DOI: 10.1088/0953-2048/26/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

Solution-derived YBa2Cu3O7nanocomposite films with a Ba2YTaO6secondary phase for improved superconducting properties

Abstract: We report on the spontaneous segregation of double perovskite Ba 2 YTaO 6 (BYTO) nanoparticles within YBa 2 Cu 3 O 7 (YBCO) films forming a nanocomposite with two ternary oxides by the low cost and scalable chemical solution trifluoroacetate approach. Phase orientation, nanostructural and pinning studies are carried out by 2D x-ray diffraction, advanced scanning transmission electron microscopy and transport measurements, respectively. In this complex oxide nanocomposite system (YBCO-BYTO) the majority of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 41 publications
4
51
0
Order By: Relevance
“…The CSD methods excel in their low investment costs and scalability compared to vacuum techniques while the growth mechanisms are deeply modified [17][18][19][20][21][22][23][24][25][26]. In this case, complex solutions are prepared where the salts used to prepare YBCO (trifluoroacetates, TFA) are extended to a fourth element (Zr, Hf, Sn, Ta) through soluble metal-organic salts with the desired stoichiometry to achieve secondary phases such as BaZrO 3 , BaSnO 3 , BaHfO 3 , Ba 2 YTaO 6 , etc [16,[27][28][29]. This single solution precursor leads, after deposition and growth, to a spontaneous segregation of two separate oxide phases (in-situ nanocomposite approach).…”
Section: Introductionmentioning
confidence: 99%
“…The CSD methods excel in their low investment costs and scalability compared to vacuum techniques while the growth mechanisms are deeply modified [17][18][19][20][21][22][23][24][25][26]. In this case, complex solutions are prepared where the salts used to prepare YBCO (trifluoroacetates, TFA) are extended to a fourth element (Zr, Hf, Sn, Ta) through soluble metal-organic salts with the desired stoichiometry to achieve secondary phases such as BaZrO 3 , BaSnO 3 , BaHfO 3 , Ba 2 YTaO 6 , etc [16,[27][28][29]. This single solution precursor leads, after deposition and growth, to a spontaneous segregation of two separate oxide phases (in-situ nanocomposite approach).…”
Section: Introductionmentioning
confidence: 99%
“…A twofold improvement in J c value by the addition of BaTiO 3 in YBCO films was reported by Jha et al [18]. Similarly, rapid enhancement in flux pinning and critical current density was observed in YBCO films by the incorporation of nanoparticles such as BaSnO 3 [9], BaHfO 3 [22] Ba 2 YTaO 6 [23], Ba 2 YNbO 6 [24,25] and Ba 2 RETaO 6 [26]. In our earlier works, we had reported the effect of addition of simple oxide, HfO 2 [27], ABO 3 type perovskite, nano BaHfO 3 [28,29] and double perovskite YBa 2 HfO 5.5 [30] tremendous improvement in flux pinning force and critical current density.…”
Section: Introductionmentioning
confidence: 58%
“…It has been demonstrated that the presence of these randomly oriented nanoparticles induces the formation of a large density of stacking faults that produce strong lattice distortions in the YBCO matrix, which act as very efficient strong isotropic pinning centers [10,30]. YBCO films with BaZrO 3 (BZO) nanoparticles, for example, have shown enhanced pinning forces (75 GN/m 2 and 600 GN/m 2 at 3 T, 65 K and 9 T, 10 K, respectively) [4], more than five times larger than standard films grown by the same process [10].…”
Section: Artificial Pinning Centers In Csd-ybco Filmsmentioning
confidence: 99%